Observation of rituximab as initial treatment in patients with minimal change disease- a retrospective study - Wang, Sha; Liang, Hua; Li, Lu-Yao; Cheng, Miao-Miao; Lv, Fang-Yi; Zong, Li; Zhao, Ke; Xiao, Xiao-Yan; Yang, Xiang-Dong (Frontiers in Immunology, 2025)
Research backgroundThis study was aimed to retrospectively investigate the efficacy and safety of rituximab (RTX) versus glucocorticoids (GC) as initial treatments for patients with minimal change disease (MCD).Research methodsPatients who were diagnosed with MCD through kidney biopsy and received RTX or GC as the initial treatment regimen were included and matched by propensity score (ratio: 1:1) based on age, sex, urine protein, and eGFR. The 2 groups each consist of 12 adult patients and 2 pediatric patients. We primarily observed the clinical remission rate at 24-week, the time to induction of remission in each group, the time to first relapse-free survival, relapse rate, as well as the changes in the urine protein-to-creatinine ratio and serum albumin levels compared to baseline during the treatment period. The incidence of adverse effects was also observed in 2 groups during the whole period.Research resultsAll 28 patients (100.00%) achieved clinical remission, with 22 patients (78.57%) achieving complete remission (CR) and 6 patients (21.43%) achieving partial remission (PR) at 24-week. The median time to remission was 5 (3-7) weeks. During the 24-week follow-up, the RTX group and the GC group each had 2 patients with recurrence, resulting in a relapse rate of 14.29%. Both the RTX group and the GC group had 14 patients (100%) achieve clinical remission, with 11 patients (78.57%) reaching CR and 3 patients (21.43%) achieving PR. The median time to remission in the RTX group was 5 (3-7) weeks, while in GC group, it was 5 (3-8) weeks (p=0.728). Follow-up results at 24 weeks indicated that the UPCR levels for all MCD patients decreased from an average of 8.93 (range 6.13-17.48) g/g to 0.07 (range 0.03-0.28) g/g, with no statistically significant difference between 2 groups (P=0.945). Serum albumin levels increased from 18.60 ± 7.54 g/L to 44.39 ± 4.50 g/L, with no significant intergroup difference (P=0.601). In the RTX group, patients tolerated RTX well, with only 1 case of tachycardia occurring during infusion, which resolved spontaneously after reducing the infusion rate. In the GC group, there were no severe adverse reactions reported. However, 10 patients experienced weight gain, 3 patients exhibited elevated blood glucose levels, 2 patients presented with skin striae, and 1 patient showed elevated transaminases.ConclusionThe use of RTX can effectively induce and maintain remission in MCD patients, demonstrating efficacy comparable to those treated with GC. Furthermore, the safety profile is favorable, making it a viable alternative to GC therapy. This provides a reliable initial treatment option for patients with MCD, particularly for pediatric patients.